Do We Know How to Avoid OASIs in Non-Supine Birth Positions? A Retrospective Cohort Analysis - Zilma Silveira Nogueira Reis; Glaucia Miranda Varella Pereira; Anna Laura Freitas Vianini; Marilene Vale Castro Monteiro; Regina Amélia Lopes Pessoa Aguiar (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2019)
Abstract Objective To evaluate the association between the upright and supine maternal positions for birth and the incidence of obstetric anal sphincter injuries (OASIs). Methods Retrospective cohort study analyzed the data of 1,728 pregnant women who vaginally delivered live single cephalic newborns with a birth weight of 2,500 g. Multiple regression analyses were used to investigate the effect of the supine and upright positions on the incidence of OASIs after adjusting for risk factors and obstetric interventions. Results In total, 239 (13.8%) births occurred in upright positions, and 1,489 (86.2%) in supine positions. Grade-III lacerations occurred in 43 (2.5%) patients, and grade-IV lacerations occurred in 3 (0.2%) women. Supine positions had a significant protective effect against severe lacerations, odds ratio [95% confidence interval]: 0,47 [0.22- 0.99], adjusted for the use of forceps 4.80 [2.15-10.70], nulliparity 2.86 [1.44-5.69], and birth weight 3.30 [1.56-7.00]. Anesthesia (p<0.070), oxytocin augmentation (p<0.228), shoulder dystocia (p<0.670), and episiotomy (p<0.559) were not associated with the incidence of severe lacerations. Conclusion Upright birth positions were not associated with a lower rate of perineal tears. The interpretation of the findings regarding these positions raised doubts about perineal protection that are still unanswered.